Biolistic Transformation of Haematococcus pluvialis With Constructs Based on the Flanking Sequences of Its Endogenous Alpha Tubulin Gene - Yuan, Guanhua; Xu, Xiaoying; Zhang, Wei; Zhang, Wenlei; Cui, Yulin; Qin, Song; Liu, Tianzhong (Frontiers in Microbiology, 2019)
Haematococcus pluvialis has high commercial value, yet with low development of genetic transformation systems. In this research, the endogenous 5’ and 3’ flanking sequences of a constitutive alpha tubulin (tub) gene were cloned along with its encoding region in H. pluvialis, in which some putative promoter elements and polyadenylation signals were identified respectively. And three selection markers of tub/aadA, tub/hyr and tub/ble with 3 different antibiotic-resistance genes fused between the endogenous tub promoter (Ptub) and terminator (Ttub) were constructed and utilized for biolistic transformation of H. pluvialis. Stable resistant colonies with introduced aadA gene were obtained after bombardments of either H. pluvialis NIES144 or SCCAP K0084 with the tub/aadA cassette, the efficiency of which could reach up to 3×10-5 per μg DNA through an established manipulation flow. And two key details, including utilization of a culture with motile flagellates dominant and controlled incubation of them on membrane filters during bombardments, were disclosed firstly. In obtained transformants, efficient integration and transcription of the foreign tub/aadA fragments could be identified through genome PCR examination and qPCR analysis, nonetheless with random style instead of homologous crossover in the H. pluvialis genome. The presented selection marker and optimized transforming procedures in this report would strengthen the platform for genetic manipulation and modification of H. pluvialis.